Parallels with the female athlete triad in male athletes - Tenforde, A. S.; Barrack, M. T.; Nattiv, A.; Fredericson, M. (Sports Medicine, 2016)
Participation in sports offers many health benefits to athletes of both sexes. However, subsets of both female and male athletes are at increased risk of impaired bone health and bone stress injuries. The Female Athlete Triad (Triad) is defined as the interrelationship of low energy availability (with or without disordered eating), menstrual dysfunction, and low bone mineral density. The Triad may result in health consequences, including bone stress injuries. Our review presents evidence that an analogous process may occur in male athletes. Our review of the available literature indicates that a subset of male athletes may experience adverse health issues that parallel those associated with the Triad, including low energy availability (with or without disordered eating), hypogonadotropic hypogonadism, and low bone mineral density. Consequently, male athletes may be predisposed to developing bone stress injuries, and these injuries can be the first presenting feature of associated Triad conditions. We discuss the evidence for impaired nutrition, hormonal dysfunction, and low bone mineral density in a subset of male athletes, and how these health issues may parallel those of the Triad. With further research into the mechanisms and outcomes of these health concerns in active and athletic men, evidence-based guidelines can be developed that result in best practice.